Diplomacy for survival: CARICOM states in a world of change - Searwar, Lloyd ed. (Freidrich Ebert Stiftung KingstonJM, 1991)
Presents a number of papers which focus on various aspects of the theme. Identifies major challenges to the continuing effectiveness of the traditional foreign policies and diplomatic approach of CARICOM states. Considers effects of the disappearance of East/West conflict from the Caribbean Basin and waning of the cold war on the capacity of regional states to attract investment and aid. Discusses internal structural factors and the scarcity of economic and human resources within which CARICOM states must devise for survival, a new foreign policy and an effective diplomatic instrument. A final paper by the editor considers the possible shape of a new diplomacy for CARICOM.